After the PC. (Economist, 1998)
Discusses the devices which look to replace the personal computer (PC) as the most popular computing device. Television set-top boxes; Fixed-screen telephones; Smart mobile phones; Handheld computers; Personal digital assistants (PDA); Network computers (NC); Reasons for the expected decline of the PC; The role of the Internet and the Java programming language.